2018
DOI: 10.3389/fimmu.2018.01704
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Lipopolysaccharide- and Lipoprotein-Induced Inflammation by Antitoxin Peptide Pep19-2.5

Abstract: The most potent cell wall-derived inflammatory toxins (“pathogenicity factors”) of Gram-negative and -positive bacteria are lipopolysaccharides (LPS) (endotoxins) and lipoproteins (LP), respectively. Despite the fact that the former signals via toll-like receptor 4 (TLR4) and the latter via TLR2, the physico-chemistry of these compounds exhibits considerable similarity, an amphiphilic molecule with a polar and charged backbone and a lipid moiety. While the exterior portion of the LPS (i.e., the O-chain) repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 31 publications
1
50
0
Order By: Relevance
“…[22][23][24] According to some studies, the anti-inflammatory activity of peptides is tightly associated with their capacity to neutralize LPS. 43,44,55 Cationic AMPs engage in strong electrostatic interactions with the negatively charged LPS, and their positive charge enables stable embedment in amphiphilic LPS micelles. 44,55,56 It has been demonstrated that a high positive charge can strengthen the ability of AMPs to bind, neutralize, and inactivate LPS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[22][23][24] According to some studies, the anti-inflammatory activity of peptides is tightly associated with their capacity to neutralize LPS. 43,44,55 Cationic AMPs engage in strong electrostatic interactions with the negatively charged LPS, and their positive charge enables stable embedment in amphiphilic LPS micelles. 44,55,56 It has been demonstrated that a high positive charge can strengthen the ability of AMPs to bind, neutralize, and inactivate LPS.…”
Section: Discussionmentioning
confidence: 99%
“…The enhanced LPS-neutralizing activity of C-L may be mainly attributed to its higher net positive charge, consistent with previous studies. 43,44,55,56,103 A higher net positive charge, therefore, should be considered when designing anti-inflammatory peptides and hybridizing is a good approach for achieving this aim. In addition, the present results suggest that C-L has potential to serve as a therapeutic drug for neutralizing endotoxin, substituting the traditional agent PMB, a well-known cyclic hydrophobic F I G U R E 1 1 C-L treatment do not alter the lipid rafts on the RAW264.7 macrophages membrane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the stronger LPS-binding affinity of (lin-SB056-1) 2 -K compared to its monomeric counterpart could be explained by its lower susceptibility to the inhibitory effect of different experimental factors (e.g., salts, proteases, macromolecules and/or cellular components) on the establishment of electrostatic interactions [49,50]. Such peptide-LPS interactions could hamper LPS to assume an optimal folding for the binding to its receptors on effector cells with consequent reduction in the pro-inflammatory response [9,51]. Alternatively, as only monomeric forms of LPS are able to trigger cell activation, the dendrimeric peptide could act by inducing LPS aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic infection and inflammation are, for example, observed in Pseudomonas aeruginosa lung infections in cystic fibrosis (CF) patients [6]. Hence, due to their dual (anti-bacterial and immunomodulatory) mechanism of action, AMPs are gaining increasing interest for the management of chronic infections [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%